Diversidade genética e citogenética em Astrocaryum spp. (Arecaceae) - Oliveira, Natália Padilha de (2016)
The Astrocaryum genus comprises 40 species, most of them widely used by the Amazon population, and some with great potential to the Brazilian economy. However, to date no information has been provided on the genetic diversity and cytogenetic characteristics of these species. The aim of this work was to assess the level and distribution of genetic diversity in three species of Astrocaryum genus and to characterize and compare the type of interphase nuclei, chromosome set for morphology, fluorochrome banding and in situ hybridization of four Astrocaryum spp. For genetic diversity analyses, plant material was sampled in three municipalities for A. aculeatum: Belterra, Santarém and Terra Santa; and two for both A. murumuru: Belém and Santo Antônio do Tauá; and A. paramaca: Belém and Ananindeua, all located in Pará state, Brazil. Thirteen microsatellite loci were tested in multiplex sets, of which eight amplified well and were used for genetic analysis. For cytogenetic study, analyses consisting of interphase nucleus, fluorochrome staining, and in situ hybridization using 45S and 5S rDNA probes, and telomere sequence were carried out. Mean number of alleles per locus for A. aculeatum, A. murumuru and A. paramaca were 2.33, 2.38 and 2.06, respectively. Genetic diversity (He) varied from 0.222 in A. aculeatum to 0.254 in A. murumuru. Both FST and AMOVA showed most of the genetic variation is found within populations for the three species, but high genetic differentiation among populations were found for A. aculeatum. Three loci (Aac04, Aac06 and Aac12) were not in Hardy-Weinberg equilibrium for the three species, with populations of A. paramaca showing a tendency for excess of heterozygotes (FIS = -0.144). Gene flow was high for populations of A. paramaca (Nm = 19.35). Karyological data for all species were first relate. The four species showed 2n = 30 chromosomes, but differences in the karyotypic formula, number and position of CMA+ bands and 45S sites, and position of 5S rDNA sites were observed. There was significant difference for total length of haploid set, with a 43% difference between the smallest (A. paramaca – 27.085 μm) and the highest (A. murumuru – 47.486 μm). Our results suggest that levels of genetic diversity are similar among species and most of the genetic diversity is found within populations for the species evaluated. Karyological data obtained here allow us to recognize species belonging to different subgenera of Astrocaryum.